Funciones periódicas, cuasiperiódicas y clasificación de funciones - Edwin Castro Fernández (Revista de Matemática: Teoría y Aplicaciones, 2009)
In this work we present some significative sets of functions. Following the ideas of [2] we introduce the almost periodic functions and its elementary properties. Based in [12] we give a clasification of the sets.